VALIDATION OF ANALYTICAL METHOD FOR THE DISSOLUTION TEST OF VITAMIN D3 5000 IU CHEWABLE TABLETS WITH HPLC AND STABILITY TESTING (Universitas Negeri Semarang, 2022)
Background: Vitamin D3 is a fat-soluble vitamin. The low solubility of vitamin D3 in water has attracted the researchers to develop a modification of vitamin D3 to be soluble in water, thus increasing bioavailability of vitamin D3 in the body and improving product performance in vitro and in vivo. Aim: This study aims to knowing the dissolution analysis method of vitamin D3 chewable tablets with HPLC and the stability of samples vitamin D3 5000 IU at 6th weeks of shelf life with storage conditions of 30 °C ± 2 ℃ and 40 °C ± 2 °C at Rh 75% ± 5%. Material and Methods: This study refers to USP 43 NF 38 with modifications of mobile phase. Results: The analytical method used shows linear results with a coefficient of correlation (r) equal to 0,9997. LoD and LoQ is 0,0076 ppm and 0,02302 ppm. The Q values of intermediate precision test were 86,431% and 85,2182%. The recovery percentage is 96,8147% - 100,1338%. The specificity test shows the analyte can be clearly distinguished from other components. In testing the stability of the test solution were 100,138% and %RSD equal to 0,12903% for 0 hours and 99,2754% and %RSD equal to 0,33193% for 24 hours. In the accelerated stability test, the results at 0 week were 85,2182%, the results at 6 weeks of 30 °C and 40°C is 86,718639% and 82,80894%. Conclucion: Validation of analytical method has met the acceptance criteria from ICH and USP.